my college hive icon mycollegehive
Groups
My College Hive notifiction icon Questions
Connect / Friends
Tags
Quiz
Books
If t = -3, then 3t^2 + 5t + 6 equals
JMAP math expression
up
0
down

If t = -3, then 3t2 + 5t + 6 equals

1) -36

2) -6

3) 6

4) 18 

27 views
Share Follow
peter
Asked by peterrep:906
University of Lagos Nigeria
24 June 2020

Comments





1 answer(s)

judziy
Judziy answeredrep:874
University of Benin Nigeria
24 June 2020
up
0
down

3t2 + 5t + 6

When t = -3, the expression becomes:

3(-3)2 + 5(-3) + 6

= 3(9) - 15 + 6

= 27 - 15 + 6

= 18

Ans 4

Share
Comments






Your Answer

my college hive loader icon



Related Tags

JMAP

2 followers

141 questions

math

2 followers

988 questions

expression

1 followers

36 questions